Molecular Diagnosis of T Cell‐Mediated Rejection in Human Kidney Transplant Biopsies. Issue 3 (28th January 2013) - Reeve, J.; Sellarés, J.; Mengel, M.; Sis, B.; Skene, A.; Hidalgo, L.; de Freitas, D. G.; Famulski, K. S.; Halloran, P. F.
<x xml:space="preserve">Abstract</x> Histologic diagnosis of T cell‐mediated rejection is flawed by subjective assessments, nonspecific lesions and arbitrary rules. This study developed a molecular test for T cell‐mediated rejection. We used microarray results from 403 kidney transplant biopsies to derive a classifier assigning T cell‐mediated rejection scores to all biopsies, and compared these with histologic assessments. The score correlated with histologic lesions of T cell‐mediated rejection (infiltrate, tubulitis). The accuracy of the classifier for the histology diagnoses was 89%. Very high and low molecular scores corresponded with unanimity among three pathologists on the presence or absence of T cell‐mediated rejection, respectively. The molecular score had low sensitivity (50%) and positive predictive value (62%) for the histology diagnoses. However, histology showed similar disagreement between pathologists—only 45–56% sensitivity of one pathologist with diagnoses of T cell‐mediated rejection by another. Discrepancies between molecular scores and histology were mostly when histology was ambiguous ("borderline") or unreliable, e.g. in cases with scarring or inflammation induced by tissue injury. Vasculitis (isolated v‐lesion TCMR) was particularly discrepant, with most cases exhibiting low TCMR scores. We propose new rules to integrate molecular tests and histology into a precision diagnostic system that can reduce errors, ambiguity and interpathologist disagreement.